O sentido de prudência na ética de Espinosa: a conciliação de uma regra prática ao vislumbre de uma sabedoria teórica - Lima, Adriana Chimenez Aviles de [UNIFESP] (2023)
This work proposes to analyze the meaning of ‘prudence’ in Spinoza’s work, however, with more emphasis on his Ethics, in which prudence operates and has its bases established in the field of knowledge and reason, as well as in the field of affections and of affective relations. However, we consider and indicate some concepts and considerations present in other texts by the philosopher, such as his Correspondence exchanged throughout his philosophical journey, and the Theological-Political Treatise. There is a desirable path for the philosopher, who seeks to conciliate practical wisdom, captured by experience, with theoretical wisdom, conquered by knowledge, in order to reach a “higher prudence” (Ch. Jaquet) resulting from an improvement to increase the potence to act and to think. Some of the concepts presented in Spinoza’s Ethics, with regard to leading man to a life that intends to be as potent as possible, contribute to the understanding of Spinoza’s notion of prudence, eg: ‘usefulness’, ‘conatus’, ‘adequate knowledge’, ‘caution’, ‘simultaneity’, ‘freedom’ and his personal motto “Cautè”. Keywords: Spinoza. Prudence. Practical rule. Theoretical wisdom.